Bypassing CFTR dysfunction in cystic fibrosis with alternative pathways for anion transport - Li, Hongyu; Salomon, Johanna J.; Mall, Marcus A. (Current opinion in pharmacology, 2017)
One therapeutic strategy for cystic fibrosis (CF) seeks to restore anion transport to affected epithelia by targeting other apical membrane Cl− channels to bypass dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) Cl− channel. The properties and regulation of the Ca2+-activated Cl− channel TMEM16A argue that long-acting small molecules which target directly TMEM16A are required to overcome CFTR loss. Through genetic studies of lung diseases, SLC26A9, a member of the solute carrier 26 family of anion transporters, has emerged as a promising target to bypass CFTR dysfunction. An alternative strategy to circumvent CFTR dysfunction is to deliver to CF epithelia artificial anion transporters that shuttle Cl− across the apical membrane. Recently, powerful, non-toxic, biologically-active artificial anion transporters have emerged.
Gesehen am 12.09.2018